Implementation of telepsychiatry in Kenya: acceptability study. Issue 3 (19th May 2022) - Kaigwa, Loice Cushny; Njenga, Frank; Ongeri, Linnet; Nguithi, Anne; Mugane, Maryanne; Mbugua, Gathoni M.; Anundo, Jacqueline; Kimari, Margaret Zawadi; Onono, Maricianah
Abstract : Background: COVID-19-related restrictions on in-person contact in healthcare, increasing psychiatric illness during the pandemic and pre-existing shortages of mental healthcare providers have led to the emergence of telepsychiatry as an attractive option for the delivery of care. Telepsychiatry has been promoted as economical and effective, but its acceptance in low- and middle-income countries is poorly understood. Aims: To explore the acceptance, experiences and perspectives of patients and healthcare providers in the uptake of telepsychiatry services in a middle-income country. Method: Focus group discussions were conducted on the WhatsApp platform with patients and care providers who have engaged in telepsychiatry. Data were analysed using a thematic approach. Results: Three main themes emerged from the five focus groups: (a) technical access, (b) user experience and (c) perceived effectiveness compared with face-to-face (in-person) interactions. Care providers reported challenges establishing rapport with the patient, particularly for initial sessions, maintaining privacy during sessions and detecting non-verbal cues on video. Patients cited internet connectivity problems, difficulty finding private space to have their sessions and cost as major challenges. Patients also felt in-person sessions were better for initial visits. Both patients and providers reported difficulties making insurance payment claims for telepsychiatry services. Overall, participants were mostly positive about telepsychiatry, citing its convenience and overall perceived effectiveness compared with in-person sessions. Conclusions: Telepsychiatry is an acceptable platform for delivery of out-patient psychiatric services in a middle-income country. Patients and providers appreciate the convenience it offers and would like it integrated as a routine mode of delivery of care.